A case of systemic lupus erythematosus with marked ascites due to idiopathic non-cirrhotic portal hypertension. (3rd April 2021) - Imabayashi, Keisuke; Nakano, Kazuhisa; Iwata, Shigeru; Tanaka, Yoshiya
Abstract: A 43-year-old-woman admitted to our department because of abdominal pain, abdominal distension, pain on both inner thighs and blurred vision lasting for 3 months. Pancytopenia and positive anti-double stranded DNA (dsDNA) antibodies were noted 5 years prior to her hospitalisation. On admission, the patient was diagnosed with systemic lupus erythematosus (SLE) with retinal vasculitis, panniculitis, cholecystitis and enteritis. The ultrasound test revealed a large amount of ascites, splenomegaly, a hypoechoic band in the liver, and portal hypertension with mildly elevated hepatic venous wedge pressure (15 mmHg). Liver biopsy showed no evidence of hepatitis, cholangitis or liver cirrhosis, leading to the diagnosis of idiopathic non-cirrhotic portal hypertension (INCPH). Prednisolone (PSL) at a daily dose of 50 mg and intravenous cyclophosphamide pulse therapy (IVCY) were initiated for SLE, while diuretics were administered for transudative ascites associated with INCPH. Although these symptoms temporarily improved, 2 months later, SLE and ascites effusion aggravated again, and portal vein thrombosis was confirmed by computed tomography. After increasing the dose of IVCY and adding an anticoagulant agent, all symptoms improved, allowing a reduction of the PSL dose. In the present case, the exacerbation of INCPH was associated with the exacerbation of SLE and the occurrence of portal thrombosis, suggesting an autoimmune and thrombotic mechanism of INCPH. On the other hand, splenomegaly, oesophageal varices, the hypoechoic band remained unchanged, suggesting the established organised INCPH was refractory to immunosuppressive agents.